Inotropic Effects of Experimental Hyperthermia and Hypothermia on Left Ventricular Function in Pigs—Comparison With Dobutamine*. Issue 3 (March 2016) - Alogna, Alessio; Manninger, Martin; Schwarzl, Michael; Zirngast, Birgit; Steendijk, Paul; Verderber, Jochen; Zweiker, David; Maechler, Heinrich; Pieske, Burkert M.; Post, Heiner
Abstract : Objectives: The results from the recent Targeted Temperature Management trial raised the question whether cooling or merely the avoidance of fever mediates better neurologic outcome in resuscitated patients. As temperature per se is a major determinant of cardiac function, we characterized the effects of hyperthermia (40.5°C), normothermia (38.0°C), and mild hypothermia (33.0°C) on left ventricular contractile function in healthy pigs and compared them with dobutamine infusion. Design: Animal study. Setting: Large animal facility, Medical University of Graz, Graz, Austria. Subjects: Nine anesthetized and mechanically ventilated closed-chest Landrace pigs (67 ± 2 kg). Interventions: Core body temperature was controlled using an intravascular device. At each temperature step, IV dobutamine was titrated to double maximum left ventricular d P /d t (1.8 ± 0.1 µg/kg/min at normothermia). Left ventricular pressure-volume relationships were assessed during short aortic occlusions. Left ventricular contractility was assessed by the calculated left ventricular end-systolic volume at an end-systolic left ventricular pressure of 100 mm Hg. Measurements and Main Results: Heart rate (98 ± 4 vs 89 ± 4 vs 65 ± 2 beats/min; all p < 0.05) and cardiac output (6.7 ± 0.3 vs 6.1 ± 0.3 vs 4.4 ± 0.2 L/min) decreased with cooling from hyperthermia to normothermia and mild hypothermia, whereas left ventricular contractility increased (left ventricular end-systolic volume at a pressure of 100 mm Hg: 74 ± 5 mL at hyperthermia, 52 ± 4 mL at normothermia, and 41 ± 3 mL at mild hypothermia; all p < 0.05). The effect of cooling on left ventricular end-systolic volume at a pressure of 100 mm Hg (hyperthermia to normothermia: –28% ± 3% and normothermia to mild hypothermia: –20% ± 5%) was of comparable effect size as dobutamine at a given temperature (hyperthermia: –28% ± 4%, normothermia: –27% ± 6%, and mild hypothermia: –27% ± 9%). Conclusions: Cooling from hyperthermia to normothermia and from normothermia to mild hypothermia increased left ventricular contractility to a similar degree as a significant dose of dobutamine in the normal porcine heart. These data indicate that cooling can reduce the need for positive inotropes and that lower rather than higher temperatures are appropriate for the resuscitated failing heart.